The comovement of credit default swap, bond and stock markets: An empirical analysis - Lars Norden; Martin Weber (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
This paper analyzes the empirical relationship between credit default swap, bond and stock markets during the period 2000-2002. Focusing on the intertemporal comovement, we examine weekly and daily lead-lag relationships in a vector autoregressive model and the adjustment between markets caused by cointegration. First, we find that stock returns lead CDS and bond spread changes. Second, CDS spread changes Granger cause bond spread changes for a higher number of firms than vice versa. Third, the CDS market is significantly more sensitive to the stock market than the bond market and the magnitude of this sensitivity increases when credit quality becomes worse. Finally, the CDS market plays a more important role for price discovery than the corporate bond market.
urn:nbn:de:hebis:30-10712
Keywords: G10; G14; C32; 330; Credit risk; Credit spreads; Credit derivatives; Lead-lag relationship; Swap; Finanzderivat; Kreditrisiko; Industrieobligation; Aktienmarkt